New applications of fractional calculus on probabilistic random variables - Dahmani, Zoubir (Acta Mathematica Universitatis Comenianae, 2017)
New results and new applications of fractional calculus for continuous random variables are presented. Some classical integral results are also generalized. On the other hand, some results (corollaries) on the paper [Fractional integral in- equalities for continuous random variables, Malaya J. Mat. 2(2014), 172{179] are corrected.
Keywords: Integral inequalities; Riemann-Liouville integral; random variable; frac- tional dispersion; fractional variance; fractional moment.